1997
DOI: 10.18174/njas.v45i1.527
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics (CFD) as a tool for the analysis of ventilation and indoor microclimate in agricultural buildings

Abstract: The basic concepts of CFD are presented in relation to applications in modelling the ventilation process and the resulting indoor climate of agricultural buildings. The validity and the advantages of this numerical technique are presented using 3 examples. Firstly the pressure coefficients along the roof of a 7-span Venlo-type greenhouse were calculated and compared with the corresponding experimental values. Next, the ventilation process in a single-span greenhouse was investigated and the results were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Computational fluid dynamics (CFD) has been used as a powerful tool to model fluid flow in diverse applications. For decades, CFD modeling has been employed to address indoor environmental problems and optimize the design of ventilation systems in a variety of agricultural facilities [ 6 ]. Most environment influencing factors are controllable in the CFD model and universal outputs of interest can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational fluid dynamics (CFD) has been used as a powerful tool to model fluid flow in diverse applications. For decades, CFD modeling has been employed to address indoor environmental problems and optimize the design of ventilation systems in a variety of agricultural facilities [ 6 ]. Most environment influencing factors are controllable in the CFD model and universal outputs of interest can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The need to address indoor environment problems in poultry housing has encouraged researchers to improve the design of ventilation systems by CFD modeling. Research conducted by Mistriotis and Jong investigated a broiler house with natural ventilation by developing a two-dimensional CFD model, and the simulation results revealed that the uniformity of indoor temperature and air velocity distribution was improved by installing a solar chimney [ 6 ]. Blanes-Vidal, Guijarro, Balasch, and Torres (2008) conducted four CFD simulations of airflows in a mechanically ventilated commercial poultry house to evaluate whether air velocities in European poultry houses fell within the optimal zone [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural engineers have embraced CFD modeling as a sophisticated numerical approach to simulate airflow in various agricultural production facilities to address environmental problems with specific aims, as CFD modeling is highly objective-oriented [ 14 ]. In particularly, using CFD simulations to evaluate agricultural ventilation designs is economical in terms of time and capital costs [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the agricultural engineering community has embraced computational fluid dynamics (CFD) to model airflow fields and thereby predict the performance of ventilation systems under various conditions for the sake of comprehensive design and evaluation [ 10 ]. Moreover, CFD modeling allows full control of the influencing factors and provides universal data in the computational domain for relatively little time and expense [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers have been encouraged to use CFD simulations to design better poultry housing ventilation systems to address indoor environmental problems. Mistriotis and Jong used a two-dimensional CFD model to study a broiler house with natural ventilation and found that employing a solar chimney improved indoor temperature and air velocity [ 10 ]. Seo et al evaluated airflow, indoor air temperature, and the ventilation efficiency of a naturally ventilated broiler house for four modified ventilation systems using CFD simulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%